The impact of cognitive apprenticeship on the learning of past tense forms among esl learners / Gan Shiau Hui - Gan, Shiau Hui (2012)
Accurate use of grammar, especially the use of tenses, is an important element when it comes to the learning of English. For those whose first language (L1) does not have verb conjugation, learning verb tenses in English as a second or foreign language could be confusing especially to those who lack the exposure. Studies conducted in Malaysia on error analysis found that verb tenses are among the most common errors made by secondary school students in their essays (Lim, 1976; Saadiyah Darus & Khor, 2009; Vahdatinejad, 2008) and is difficult to remedy (Saadiyah Darus & Kaladevi Subramaniam, 2009; Vijaya & Viswanath, 2010). Acknowledging the existence of the problem, this study set out to investigate an alternative teaching method which may address the issue by incorporating the use of cognitive apprenticeship in the instruction of past tense forms in narrative writing. The study aimed to investigate to what extent is cognitive apprenticeship effective in reducing tenses errors in ESL learners’ narrative writing and to gauge the perceptions of these learners about the treatment given. This study involved 51 low to intermediate level of English proficiency Form Five students (23 males and 28 females) from a vocational school in Kelantan and they were involved in a six-week treatment and administered 2 note-expansion tests (pre-test and post-test). From the results, 12 respondents representing three different groups, i.e., the most improved group, least improved group and the group which deteriorated the most in their post-test were later selected for individual interview sessions. The findings from the study revealed that the use of cognitive apprenticeship in the instruction of past tense forms helped the respondents reduce their errors in verb tenses in general and the interviewed respondents also shared their experiences and thoughts on the features and teaching methods of cognitive apprenticeship that were used during the treatment. The results supported the premise that the use of cognitive apprenticeship is beneficial to learners in language learning and therefore, proper planning in integrating the features, as well as, teaching methods of cognitive apprenticeship to learners’ learning preferences in the classroom should be made to enhance learners’ performance in English language.